The Assessment of Governance on Child Labor in evidence of Pakistan - Ali, Syed Wajahat; Gul, Faiqua (iRASD Journal of Economics, 2019)
The aim of this study is to explore the impact of Governance on Child Labor. We all know, child labor is most pressing issue in developing countries and illiteracy, less per capita income, malnutrition and lack of development has added the impact. In article, we discussed the types of Governance and explores some other factors which impede and promote the public sector responsibilities towards children. We also highlighted the methodologies of assessment and performance of governments as protectors of children rights according to international commitments i.e. SDG’s, In study, the dependent variable is Child Labor, while the independent variables are Governance, Population Growth Rate, Literacy Rate, Gross Domestic Product and Number of Schools. Time series data is used in range of 1990 to 2018. Augmented Dicky Fuller test is used to check the stationarity of the data. ARDL technique is applied on variables to check the long and short run relationship. The result shows an inverse relation between child labor and Governance, GDP, Literacy and number of schools as improvement in these indicators will decrease child labor. However, Population and child labor has a positive impact, by increasing population child labor will be increased. Impactful policies, good governance and better leadership are the only tools that can be helpful to tune child labor problem in developing countries.